ELASTIC BUCKLING OF STRAIGHT BARS - Minodora-Maria PASĂRE (Fiabilitate şi Durabilitate)
Buckling is of great importance in the operation of parts, machine parts and equipment. The forces that appear, when the buckling phenomenon manifests itself in the functioning of these machine parts, must not exceed certain values, called critical, because it can lead to the damage of these machine parts or even their destruction. Achieving the critical buckling force in a part is a dangerous condition, so in the operation of machine parts and equipment must take into account those permissible values prescribed in the literature.